LITERATUR REVIEW: PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Dika Fuji Okta; Carmel Meiden (Juremi: Jurnal Riset Ekonomi, 2024)
This study discusses the disclosure of Corporate Social Responsibility (CSR) with a focus on the factors influencing CSR practices and their impact on company performance and public perception. A qualitative research method was used, involving a literature review. Data was obtained through the collection of secondary data in the form of previous research articles. The independent variables include company size, leverage, and profitability, while the dependent variable is CSR disclosure. The literature analysis results show various outcomes, indicating the influence of company size, leverage, and profitability on CSR disclosure. Some results indicate a positive and significant influence, while others are either not significant or have no influence